Exclusionary Populism and Islamophobia: A Comparative Analysis of Italy and Spain - Laura Cervi (Religions, 2020)
Exclusionary populism is well known for twisting real grievances of the citizens, by problematizing the gap between “us” and “them”, capitalizing on identity lines, calling out as “others” those who do not share “pure people’s” identity and culture. Especially after 9/11, Muslims have become the ideal-type of “other”, making Islamophobia the primary populist anti-paradigm. This article contributes to the burgeoning literature on Islamophobic populism analyzing the presence of Islamophobia in the electoral discourse of Vox party in Spain and Lega in Italy. In addition, it makes a novel contribution by discussing and testing the existence of different models of Islamophobia, distinguishing between “banal Islamophobia” and “ontological Islamophobia”. Applying clause-based semantic text analysis—including qualitative and quantitative variables—to thirty speeches by the two party leaders, Santiago Abascal and Matteo Salvini, during the last three elections (General, Regional and European), the paper concludes that, despite the similarities, the two politician display two different models of Islamophobia. Whereas Abascal displays a clear “ontological Islamophobia”, depicting Muslims ontologically incompatible with Spanish civilization (defined precisely by its anti-Muslim history), the latter presents a mix of arguments that oscillate between “ontological” and “banal” Islamophobia.